2012
DOI: 10.4236/ojrd.2012.24014
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Serum C-Reactive Protein with Disease Severity in Tuberculosis Patients

Abstract: Purpose: To study the factors influencing sputum smear conversion including Serum C-Reactive Protein (CRP) and its correlation with disease severity in tuberculosis patients. Method: Levels of Serum-CRP concentrations were determined in 60 patients with pulmonary tuberculosis, 30 healthy volunteers and patients in follow-up after completion of antitubercular treatment (DOTS therapy). Results: Serum-CRP levels were found to be significantly higher in smear-positive group as compared with the follow-up patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 16 publications
3
8
0
Order By: Relevance
“…Similar results were reported in another study with CRP (14) , but the same was not observed for ESR marker. When CI variable and the smear were evaluated, CRP also showed a significant association (Table 3), as shown in published reports (6,22) , in which CRP levels were significantly higher in the most severe tuberculosis before starting treatment.…”
Section: Discussionsupporting
confidence: 57%
“…Similar results were reported in another study with CRP (14) , but the same was not observed for ESR marker. When CI variable and the smear were evaluated, CRP also showed a significant association (Table 3), as shown in published reports (6,22) , in which CRP levels were significantly higher in the most severe tuberculosis before starting treatment.…”
Section: Discussionsupporting
confidence: 57%
“…The difference in the CRP levels at the end of treatment was however statistically significant. Similar results were reported by Mohammad Shameemet al [12] , Peresi E et al [7] , Lee JH et al [13] and Plit ML [14] .…”
Section: Discussionsupporting
confidence: 89%
“…Study by Khalid et al [11] in pulmonary TB patients showed a similar pattern with raised overall mean CRP in patients with a mean of 9.87±4.83 in cases and serum CRP was 2.76±1.34 in controls (p 0.01). Shameem et al [12] in their study from north India found results comparable to our study. They found serum-CRP levels to be significantly higher at baseline (43.65 ± 23.68), as compared with the follow-up patients (9.88 ± 5.23).This study also studied changes in serum CRP concentration during treatment with regimen of antitubercular therapy.…”
Section: Discussionsupporting
confidence: 80%